Is traditional marketing mix still suitable for hotel banquets? An empirical study of banquet marketing in five-star hotels - Yin, Jie; Fang, Sha; Cheng, Yun (Frontiers in Psychology, 2022)
Are traditional marketing mix strategies still suitable for hotel banquet marketing? Using the binary logistic regression analysis method, this study used 763 banquet sales records at the Quanzhou Hilton Hotel to comprehensively test the influence of traditional marketing mix strategies on banquet marketing effects. By focusing on new marketing methods (such as video, the Internet, and WeChat marketing), this study tested the effectiveness of traditional marketing strategies in the new media era. The findings revealed that a combination of products is easier to market than a single product, whereas price is still a key factor in hotel banquet marketing. However, sales channels and personal identity have no significant effects on banquet marketing. Finally, based on the failure cases analysis, this study proposed a feasible path for promoting banquet marketing.